Salahuddin al-Idlibī’s methodology of hadith matn criticism: An analysis of the hadith of the fly in a drink - Chamelia Bunga Nurani; Eva Kumalasari; Nur Efendi (Mishkat: Journal of Theology and Civilization, 2026)
Debates surrounding the authenticity of hadith remain prominent in contemporary scholarship, particularly regarding traditions perceived to conflict with reason and modern science. This study examines Salahuddin al-Idlibī’s methodology of matn criticism by applying its four evaluative criteria to the hadith of the fly narrated in Ṣaḥīḥ al-Bukhārī. Employing a qualitative library research approach, data were collected through documentation and analyzed using content analysis and descriptive-analytical methods. The analysis is based on four criteria: conformity with the Qur'an, consistency with more authentic hadiths, compatibility with reason, historical facts and scientific knowledge, and the linguistic characteristics of the Prophet's sayings. The findings show that the hadith fulfills all four criteria. Its content is consistent with the Qur'an and authentic hadiths, is rationally understandable in light of historical context and scientific findings, and reflects the Prophet's linguistic style. Therefore, al-Idlibī’s methodology is both conceptually sound and practically applicable for evaluating debated hadiths. Abstrak Perdebatan mengenai autentisitas hadis masih menjadi perhatian dalam kajian kontemporer, terutama terhadap hadis yang dianggap bertentangan dengan akal dan ilmu pengetahuan modern. Penelitian ini bertujuan mengkaji metodologi kritik matan Salahuddin al-Idlibī dengan menerapkan empat kriterianya pada hadis lalat dalam minuman yang diriwayatkan dalam Ṣaḥīḥ al-Bukhārī. Penelitian menggunakan pendekatan kualitatif dengan metode studi kepustakaan. Data dikumpulkan melalui dokumentasi dan dianalisis menggunakan analisis isi serta metode deskriptif-analitis. Analisis didasarkan pada empat kriteria, yaitu kesesuaian dengan Al-Qur'an, keselarasan dengan hadis yang lebih sahih, kesesuaian dengan akal, fakta sejarah, dan ilmu pengetahuan, serta karakteristik kebahasaan sabda Nabi. Hasil penelitian menunjukkan bahwa hadis tersebut memenuhi keempat kriteria. Dengan demikian, metodologi kritik matan Salahuddin al-Idlibī memiliki landasan konseptual yang kuat sekaligus relevan diterapkan dalam mengkaji hadis-hadis yang masih diperdebatkan pada era kontemporer.